The effect of the catalyst and the type of ionic liquid on the hydrosilylation process under batch and continuous reaction conditions. (8th March 2018) - Jankowska-Wajda, M.; Kukawka, R.; Smiglak, M.; Maciejewski, H.
Abstract : We present a simplified method for performing the hydrosilylation reaction in a heterogeneous catalytic system with the use of ionic liquids and microreactor systems. Abstract : Organofunctional silanes, siloxanes, and polysiloxanes are widely applied in industry. One of the most popular and commonly used processes for the synthesis of these compounds is based on the catalytic hydrosilylation reaction. However, even though this reaction was widely investigated in homogeneous single-phase systems, there is still a large problem with later separation of the catalyst from the product after completion of the reaction. One of the solutions to this problem is use of ionic liquids to create a biphasic system with substrates, where the catalyst is dissolved in the ionic liquid phase, and this phase can be easily separated and reused. Moreover, optimization and intensification of the process can be improved by using continuous flow-through reactors on a microscale (microreactors) due to significantly larger surface-to-volume ratios and microstructured internal volumes of the reactors, allowing much more efficient heat exchange. In our studies, we have investigated, as a model, the reaction between 1, 1, 1, 3, 5, 5, 5-heptamethyltrisiloxane and 1-octene, using a series of platinum and rhodium catalysts dissolved in four different ionic liquids in batch and in the microreactor system. Studies have shown that the use of ionic liquids in general allows for catalyst recycling and reuse in subsequent reaction cycles. Moreover, the use of microreactors intensified the process, allowing a higher yield to be obtained than under conventional batch reaction conditions.